Alpha-peptide receptor radionuclide therapy using actinium-225 labeled somatostatin receptor agonists and antagonists - Shi, Mengqi; Jakobsson, Vivianne; Greifenstein, Lukas; Khong, Pek-Lan; Chen, Xiaoyuan; Baum, Richard P.; Zhang, Jingjing (Frontiers in Medicine, 2022)
Peptide receptor radionuclide therapy (PRRT) has over the last two decades emerged as a very promising approach to treat neuroendocrine tumors (NETs) with rapidly expanding clinical applications. By chelating a radiometal to a somatostatin receptor (SSTR) ligand, radiation can be delivered to cancer cells with high precision. Unlike conventional external beam radiotherapy, PRRT utilizes primarily β or α radiation derived from nuclear decay, which causes damage to cancer cells in the immediate proximity by irreversible direct or indirect ionization of the cells’ DNA, which induces apoptosis. In addition, to avoid damage to surrounding normal cells, PRRT privileges the use of radionuclides that have little penetrating and more energetic (and thus more ionizing) radiations. To date, the most frequently radioisotopes are β– emitters, particularly Yttrium-90 (90Y) and Lutetium-177 (177Lu), labeled SSTR agonists. Current development of SSTR-targeting is triggering the shift from using SSTR agonists to antagonists for PRRT. Furthermore, targeted α-particle therapy (TAT), has attracted special attention for the treatment of tumors and offers an improved therapeutic option for patients resistant to conventional treatments or even beta-irradiation treatment. Due to its short range and high linear energy transfer (LET), α-particles significantly damage the targeted cancer cells while causing minimal cytotoxicity toward surrounding normal tissue. Actinium-225 (225Ac) has been developed into potent targeting drug constructs including somatostatin-receptor-based radiopharmaceuticals and is in early clinical use against multiple neuroendocrine tumor types. In this article, we give a review of preclinical and clinical applications of 225Ac-PRRT in NETs, discuss the strengths and challenges of 225Ac complexes being used in PRRT; and envision the prospect of 225Ac-PRRT as a future alternative in the treatment of NETs.